Ball-milled bismuth oxybromide/biochar composites with enhanced removal of reactive red owing to the synergy between adsorption and photodegradation. (15th April 2022) - Luo, Yidan; Han, Yu; Xue, Mingshan; Xie, Yu; Yin, Zuozhu; Xie, Chan; Li, Xibao; Zheng, Yulin; Huang, Jinsheng; Zhang, Yue; Yang, Yicheng; Gao, Bin
Abstract: In this paper, bismuth oxybromide (BiOBr)/biochar composites were synthesized by a facile ball milling method for synergistic adsorption and photodegradation of Reactive red 120 (RR120). The characterizations show that ball milling changed the degree of crystallization, increased the surface area, and promoted the charge transfer ability of biochar. The 70% BiOBr/BC composite showed the best removal efficiency for RR120 removal with or without light illumination, which proves its enhanced removal ability by adsorption and photodegradation. The biochar is served as a support of BiOBr for preventing its aggregation and a transporter of charges for promoting the separation of photo-induced carriers in composites. BiOBr can release the adsorption sites on the surface of composites by degradation, which facilitated the RR120 removal and regenerated the photocatalyst for reusing. The strong interactions between BiOBr and biochar in composites resulted from ball milling were beneficial for the charge transfer and synergistic removal of adsorption and degradation. Findings of this work indicate that ball milling method is an effective method to prepare highly efficient biochar-based composites for RR120 removal through synergistic adsorption and photodegradation. Graphical abstract: Image 1 Highlights: BiOBr/biochar composites were firstly synthesized by ball milling method. Biochar increased the surface area and promoted charge transfer in composites. There were strong interactions between BiOBr and biochar after ball milling. Synergy between adsorption and photodegradation in BiOBr/biochar is elucidated.